Prevalence of proton pump inhibitors drug interactions in community pharmacy: a network analysis approach. - Lorena Maria Lima de Araujo; Júlia Scarlet Batista Oliveira; Maria Vivyanne de Moura Lopes; Rafael Silva de Arruda; Antonio Gouveia Oliveira; Rand Randall Martins (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2023)
Objective: The aim of this study is to identify the prevalence of drug interaction associated with proton pump inhibitors, associated factors and drugs involved. Methods: Cross-sectional study in 194 customers (> 18 years) of community pharmacies shortly after proton pump inhibitors acquisition (March 2019 to March 2020). Risk factors for drug interaction were assessed via multivariate logistic regression and relevance by network analysis. Results: The prevalence of drug interaction was 16.4% and was related to older age (OR=1.05; 95%CI 1.03 - 1.07) and female sex (OR=2.27; 95%CI 1, 15 - 4.47). The network analysis identified drug interaction involving omeprazole and pantoprazole as the most relevant and related to the prescription of levothyroxine, clopidogrel and cilostazol. Conclusion: The drug interaction among proton pump inhibitors users increase with age and are more common in women, especially those associated with levothyroxine, cilostazol and clopidogrel.